PRIORITIZATION OF TOURISM TYPES USING FUZZY ANALYTIC NETWORK PROCESS - Demirel, Tufan; Demirel, Nihan Cetin; Ozdemir, Yavuz (WORLD SCIENTIFIC PUBL CO PTE LTD, 2010)
Recent years, tourism is one of the major business areas for countries Its effect on several disciplines can not be disclaimed For this reason investments on this sector have to be feasible and logical Which types of tourism or which investment questions must be discussed and calculated numerically In this paper, tourism types for Turkey is pritionzed by using fuzzy analytic network process and this paper guides investors for feasible investments.
Keywords: SELECTION; Operations Research & Management Science